2012
DOI: 10.1177/193758671200500407
|View full text |Cite
|
Sign up to set email alerts
|

Sound Levels, Staff Perceptions, and Patient Outcomes During Renovation Near the Neonatal Intensive Care Unit

Abstract: Construction above the NICU did not cause substantially louder sound levels, but staff perceived important changes in noise and work routines. No evidence suggested that patients were negatively affected by the renovation period. Meticulous construction planning remains necessary to avoid interference with patient care and caregiver work environments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Observational and experimental studies suggested that noise can increase annoyance levels (2,3), undermine sleep quality and cause daytime drowsiness (4), worsen patient outcomes and staff performance in hospitals (5), and impair cognitive performance in school children (6,7). It may induce these physiological and psychosocial responses, and ultimately extra-auditory system disorders, by stimulating the hypothalamus-pituitary-endocrine system and by altering blood dynamics and hormone levels (8).…”
Section: Introductionmentioning
confidence: 99%
“…Observational and experimental studies suggested that noise can increase annoyance levels (2,3), undermine sleep quality and cause daytime drowsiness (4), worsen patient outcomes and staff performance in hospitals (5), and impair cognitive performance in school children (6,7). It may induce these physiological and psychosocial responses, and ultimately extra-auditory system disorders, by stimulating the hypothalamus-pituitary-endocrine system and by altering blood dynamics and hormone levels (8).…”
Section: Introductionmentioning
confidence: 99%
“…In the case of neonates, it is correlated to alterations in heart rate, blood pressure, and oxygen saturation (Williams et al, 2009;Smith et al, 2018). Conversely, questionnaires and interviews are the classical methods used to evaluate staff tolerance and awareness toward sound (Darcy et al, 2008;Trickey et al, 2012). However, studies focusing on the repercussions of the sound environment on parents are scarce, if not absent.…”
Section: Figurementioning
confidence: 99%
“…Construction noise levels compound when tasks are completed indoors where sound reverberates off interior walls, often the case related to hospital construction (Ulrich & Zimring, 2004). In a prospective study of sound levels, staff perceptions, and patient outcomes during renovation directly above a 104-bed NICU (N ¼ 3,127), Trickey, Arnold, Parmar, and Lasky (2012) reported no difference in pre-, concurrent-, and postconstruction NICU length of stay. Of note, the NICU contained sound absorbing materials including carpeting in large patient bays and acoustic tile ceilings and infant auditory function was not evaluated.…”
Section: Construction Noisementioning
confidence: 99%